Pengaruh Lifestyle, Literasi Keuangan, Kontrol Diri, Dan E-Money Terhadap Perilaku Konsumtif Mahasiswa Akuntansi Di Surakarta - Anita, Tri; Hidayah, Nur Endah Fajar (ProBank, 2024)
The phenomenon underlying this research is the development of digital technology and the high marketing stimulus from the marketplace that triggers the consumer behavior of accounting students in Surakarta. The study's goal was to examine how Surakarta accounting students' purchasing habits were impacted by their lifestyle, financial literacy, self-control, and e-money. 1264 accounting students in Surakarta made up the population; 187 individuals were selected for this study using accidental sampling as the sampling method. Validity and reliability tests were performed on a questionnaire employed in the data gathering method. Multiple linear regression analysis was employed as the data analysis method. The study's findings demonstrated that while financial literacy and self-control had no discernible impact on student consumer behavior, lifestyle and e-money had a favorable and significant impact on accounting students' purchasing habits in Surakarta.